Stabilization of an iridium oxygen evolution catalyst by titanium oxides. (31st March 2021) - Kasian, Olga; Li, Tong; Mingers, Andrea M; Schweinar, Kevin; Savan, Alan; Ludwig, Alfred; Mayrhofer, Karl
Abstract: The anodic oxygen evolution reaction (OER) has significant importance in many electrochemical technologies. In proton exchange membrane water electrolyzers it plays a pivotal role for electrochemical energy conversion, yet sluggish kinetics and the corrosive environment during operation still compel significant advances in electrode materials to enable a widespread application. Up-to-date Iridium is known as the best catalyst material for the OER in acidic media due to its relatively high activity and long-term stability. However, scarcity of iridium drives the development of strategies for its efficient utilization. One promising way would be the formation of mixtures in which the noble catalyst element is dispersed in the non-noble matrix of more stable metals or metal oxides. A promising valve metal oxide is TiOx, yet the degree to which performance can be optimized by composition is still unresolved. Thus, using a scanning flow cell connected to an inductively coupled plasma mass spectrometer, we examined the activity and stability for the OER of an oxidized Ir–Ti thin film material library covering the composition range from 20–70 at.% of Ir. We find that regardless of the composition the rate of Ir dissolution is observed to be lower than that of thermally prepared IrO2 . Moreover, mixtures containing at least 50 at.% of Ir exhibit reactivity comparable to IrO2 . Their superior performance is discussed with complementary information obtained from atomic scale and electronic structure analysis using atom probe tomography and x-ray photoelectron spectroscopy. Overall, our data shows that Ir–Ti mixtures can be promising OER catalysts with both high activity and high stability.